2021
DOI: 10.1111/1467-8489.12452
|View full text |Cite
|
Sign up to set email alerts
|

Market integration of domestic and imported seafood: Insights from the Sydney Fish Market*

Abstract: Australia has experienced a significant increase in seafood imports over the past two decades. Concurrently, Australian seafood producers have raised concerns that the low market prices of imported fish may negatively affect the prices of domestically produced seafood and, subsequently, the profitability of the Australian fishing industries. To validate this concern, this study examines the relationship between prices of domestically produced seafood and imported fish. Price data from the Sydney Fish Market (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…On the other hand, with smaller quantiles, the impact of market size is becoming more significant. This supports the findings of Climent-Pérez et al ( 2023), Schrobback et al (2022), andPincinato, Gasalla, et al (2022);Pincinato, Oglend, et al (2022), which showed that market efficiency drives the fisheries sector to attain sustainable competitiveness. Additionally, in the medium and most recent quantiles, there is a strong and positive correlation between the results of intellectual property rights and fisheries productivity.…”
Section: Panel Estimation Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, with smaller quantiles, the impact of market size is becoming more significant. This supports the findings of Climent-Pérez et al ( 2023), Schrobback et al (2022), andPincinato, Gasalla, et al (2022);Pincinato, Oglend, et al (2022), which showed that market efficiency drives the fisheries sector to attain sustainable competitiveness. Additionally, in the medium and most recent quantiles, there is a strong and positive correlation between the results of intellectual property rights and fisheries productivity.…”
Section: Panel Estimation Resultssupporting
confidence: 90%
“…This supports the growth theory for the panel of nations that produce fisheries. The main finding of Climent‐Pérez et al (2023), and Schrobback et al (2022)—that market size has a positive and inelastic influence on the growth of the fisheries industry—is echoed by this outcome. The European fish industry is thriving for several reasons, chief among them the increasing spending by Europeans on fish and shellfish despite their higher pricing.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation